2021
DOI: 10.4236/ojtr.2021.91002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hand Care Therapy and Garden Walks That Are Conscious of the Stimulation of the Five Senses for Recovery of Cognitive and Mental and Physical Dysfunction Caused by COVID-19

Abstract: The Japan Dementia Prevention Society conducted a questionnaire survey of dementia specialists conducted in August 2020. Regarding the worsening of symptoms in people with dementia, 8% answered that they "accept more" and 32% answered that they "recognize a minority". In the previous research report (Open Journal of Therapy and Rehabilitation Vol.8 No.3), we examined whether hand care therapy (HCT) as one of the passive horticultural therapy was effective in preventing dementia/MCI. Start of the test in August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In contrast, our study visually demonstrated the healing impact of natural landscapes. Koura et al (2021) employed virtual reality (VR) technology to replicate real natural settings, affirming their therapeutic influence in a threedimensional virtual context. Our research shows that even two-dimensional images of natural landscapes possess healing properties.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study visually demonstrated the healing impact of natural landscapes. Koura et al (2021) employed virtual reality (VR) technology to replicate real natural settings, affirming their therapeutic influence in a threedimensional virtual context. Our research shows that even two-dimensional images of natural landscapes possess healing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral restrictions caused by the onslaught of the new coronavirus (commonly known as COVID-19, virus name: SARS-CoV-2) and its mutant strains have resulted in an increasing number of elderly people suffering not only cognitive but also physical and mental damage [3] [4] [5]. The authors suggest that horticulture, which takes into account human-plant relationships, can be easily introduced as an occupational therapy technique if it is familiar to the elderly and has passive benefits such as placing oneself in that environment.…”
Section: Introductionmentioning
confidence: 99%
“…The global epidemic of Covid-19 has brought about lifestyle changes such as restrictions on the range of activities of citizens in each country. In Japan, there is concern about lack of verbal or nonverbal communications and exercise for the elderly, who are said to be prone to becoming severely ill [2] [3]. And psychogeriatric medical care often takes time.…”
Section: Introductionmentioning
confidence: 99%
“…Changes appeared in muscle tension, skin conductance and pulse that correlates with reduced blood pressure [4] [5]. Various studies of horticultural therapy programs have demonstrated the positive effects on dementia protection, schizophrenic behavior and those suffering from depression [6] [7].…”
Section: Introductionmentioning
confidence: 99%